2008
DOI: 10.1080/00498250802483768
|View full text |Cite
|
Sign up to set email alerts
|

Impaired intrinsic chiral inversion activity of ibuprofen in rats with adjuvant-induced arthritis

Abstract: 1. The effects of adjuvant-induced arthritis on the chiral inversion of 'profens', a type of non-steroidal anti-inflammatory drug, have hardly been investigated. The authors investigated the effects of adjuvant-induced arthritis on the chiral inversion of ibuprofen using freshly isolated rat hepatocytes. 2. S- or R-ibuprofen was incubated with hepatocytes isolated from control and adjuvant-induced arthritis rats in the absence of the serum. In the hepatocyte system the chiral inversion rate constant of R- to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Ibuprofen (IB) as a model compound of 2-APA undergoes unidirectional chiral inversion of the inactive R-enantiomer to the active S-enantiomer in rats (Kaiser et al, 1976). We previously demonstrated that the intrinsic chiral inversion rate constant of IB and the metabolic degradation rate constants decreased in AA rats compared with those of control rats in freshly isolated rat hepatocytes (Uno et al, 2008). This in vivo study was carried out to clarify the effects of AA inflammation on the stereoselective pharmacokinetics of R-IB and S-IB and chiral inversion of IB after intravenous administration to rats.…”
Section: Introductionmentioning
confidence: 99%
“…Ibuprofen (IB) as a model compound of 2-APA undergoes unidirectional chiral inversion of the inactive R-enantiomer to the active S-enantiomer in rats (Kaiser et al, 1976). We previously demonstrated that the intrinsic chiral inversion rate constant of IB and the metabolic degradation rate constants decreased in AA rats compared with those of control rats in freshly isolated rat hepatocytes (Uno et al, 2008). This in vivo study was carried out to clarify the effects of AA inflammation on the stereoselective pharmacokinetics of R-IB and S-IB and chiral inversion of IB after intravenous administration to rats.…”
Section: Introductionmentioning
confidence: 99%